Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2337/dc07-2424
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Leg Bypass Surgery for Critical Limb Ischemia Is Poor in Patients With Diabetes

Abstract: OBJECTIVE -Our aim was to assess the risk of major amputation or death after leg bypass surgery for critical limb ischemia in patients with diabetes versus those without. CONCLUSIONS -Diabetes is associated with lower amputation-free survival after leg bypass for critical limb ischemia. Patients with diabetes and limb ischemia need intensified treatment of diabetes-related risk factors to improve outcome. RESEARCH DESIGN AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 24 publications
7
67
2
1
Order By: Relevance
“…Weiss and Sumpio reported in a meta-analysis that graft patency was equivalent in patients with and without diabetes. 18 A Swedish study found a lower amputation-free survival rate in diabetic patients after leg bypass surgery, 19 contrary to the findings of the present study. These other reports, however, included differing preoperative patient profiles, severity of disease, operative procedures and follow-up systems.…”
Section: Discussioncontrasting
confidence: 57%
“…Weiss and Sumpio reported in a meta-analysis that graft patency was equivalent in patients with and without diabetes. 18 A Swedish study found a lower amputation-free survival rate in diabetic patients after leg bypass surgery, 19 contrary to the findings of the present study. These other reports, however, included differing preoperative patient profiles, severity of disease, operative procedures and follow-up systems.…”
Section: Discussioncontrasting
confidence: 57%
“…104 In a population-based cohort of linked nationwide databases in Sweden of 1840 patients, amputation rates were 65% higher over the course of 2.2 years after lower extremity bypass surgery for critical limb ischemia in patients with diabetes mellitus compared with those without diabetes mellitus. 105 Patients with diabetes mellitus have other conditions that contribute to foot wounds and exacerbate the complications of vascular insufficiency, such as neuropathy and altered foot mechanics. The presence of these additional complications may make determination of the pathogenesis of pedal ulcers more difficult to ascertain.…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
“…Patients with foot complications are more likely to develop CLI if they are diabetic and the subsequent major amputation is higher than that in non-diabetic patients [5]. Various reports have also confirmed the risk of major amputation or death after leg bypass surgery for CLI in patients with diabetes [6].…”
Section: Introductionmentioning
confidence: 76%
“…Most reports have confirmed that the results of leg bypass surgery for CLI are poor in patients with diabetes. In all instances, aggressive surgical debridement irrespective of any anatomy remains mandatory in diabetic foot ulceration in order to reduce the chances of infection [6].…”
Section: Introductionmentioning
confidence: 99%